PREVALENSI TERJADINYA BURNOUT SYNDROME DAN HUBUNGAN DENGAN FAKTOR PENYEBABNYA PADA DOSEN WANITA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Intan Fridayanti, Dewa Ayu; Purnawati, Susy; Indah Sri Handari Adiputra, Luh Made; Tirtayasa, Ketut (Universitas Udayana, 2022)
Female workers have a high level of fatigue which can lead to burnout syndrome, especially female workers who are lecturers at Faculty of Medicine Udayana University. This study aims to determine the prevalence of burnout syndrome in female lecturers and the relationship with the causative factors. This study is an analytical observational study with a cross-sectional approach using 94 research samples. The relationship between variables was analyzed using Chi-square. The results of this study indicate that there is no significant relationship between age and burnout syndrome (p=0,140); there is no significant relationship between marital status and burnout syndrome (p=0,780); there is no significant relationship between tenure and burnout syndrome (p=0,238); there is no significant relationship between individual factors and burnout syndrome (p=0,347); there is no significant relationship between organizational factors and burnout syndrome (p=0,331); there was no significant relationship between work environment and burnout syndrome (p=0,202). The conclusion of the study is that there is no relationship between age, marital status, tenure, individual factor, organizational factor and work environment with the occurrence of burnout syndrome